Dramatic Changes in Oncology Care Pathways During the COVID‐19 Pandemic: The French ONCOCARE‐COV Study. (11th November 2020) - Brugel, Mathias; Carlier, Claire; Essner, Christine; Debreuve‐Theresette, Adeline; Beck, Marie‐Françoise; Merrouche, Yacine; Bouché, Olivier
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic may have affected cancer management. We aimed to evaluate changes in every oncology care pathway essential step, from screening to treatment, during the pandemic. Monthly oncological activity differences between 2019 and 2020 (screening tests, histopathological analyzes, multidisciplinary tumor board meetings (MTBMs), diagnostic announcement procedures (DAPs), and treatments were calculated in two French areas experiencing different pandemic intensity (Reims and Colmar). COVID‐19 has had a dramatic impact in terms of screening (−86% to −100%), diagnosis (−39%), and surgical treatment (−30%). This global decrease in all essential oncology care pathway steps contrasted with the relative stability of chemotherapy (−9%) and radiotherapy use (−16%). Outbreak occurred earlier and with more intensity in Colmar but had a comparable impact in both areas regarding MTMBs and DAPs. The current ONCOCARE‐COV study is still in progress and with a longer follow‐up to analyze postlockdown situation. Abstract : The COVID‐19 pandemic may have affected cancer management. This article evaluates the changes in oncological care pathways during the COVID‐19 crisis, based on results of the ONCOCARE‐COV study.